The Concept and Virtue of Tauhid in Kitab At-Tauhid by Shaykh Muhammad bin Abdul-Wahhab: An Analytical Study of Chapters One and Two: - - Ainaya Azahra; Sakinah Rahmania Bajubair; Agung Pranoto Kadiatmaja (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine the concept and significance of Tauhid (the Oneness of Allah) as presented in Kitab At-Tauhid by Shaykh Muhammad ibn Abd al-Wahhab, with a focus on the first two chapters: “At-Tauhid” and “The Virtue of Tauhid and Its Expiation of Sins.” This research employs a qualitative method using a library research approach by analyzing primary and secondary sources, including the Qur’an, authentic hadiths, and classical Islamic commentaries. The findings reveal that Tauhid is not merely a theological doctrine but a transformative principle that purifies the heart, strengthens faith, and shapes moral character. Shaykh ibn Abd al-Wahhab’s reformist effort sought to restore the purity of Islamic monotheism and eliminate deviant practices such as reliance on intermediaries and saint veneration. This study concludes that Tauhid possesses enduring spiritual and ethical relevance in addressing contemporary moral crises, materialism, and secularism, functioning as a foundational framework for faith renewal, moral integrity, and universal harmony.